We need long-term commitments in the form of public investment' - Marc Lavoie (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
Mario, how did you become an economist? When I finished high school in Montreal, I really had no idea what I was going to study and economics was not on my radar. I had to take a bunch of courses that were compulsory for the programme of arts and sciences at McGill University where I had chosen to pursue my undergraduate studies. The norm was to take five two-semester courses. So, I registered in courses such as English literature, political science, philosophy, history, and also a two-semester differential and integral calculus course. But friends of mine were taking six courses
Keywords: 330